Enhancing service delivery via Work-Integrated Learning (WIL) at uMzimkhulu Local Municipality, South Africa - Sikhona Cornelius Nkosi; Linah Mahlahla; Kunle Oparinde (Interdisciplinary Journal of Rural and Community Studies)
Municipalities in South Africa face numerous challenges that hinder efficient service delivery. One of these challenges is the lack of implementation of required services, leading to citizen dissatisfaction and protest actions. This study aims to investigate methods for improving service delivery in public institutions in South Africa through the implementation of work-integrated learning (WIL) programmes. Data for this study was collected from the uMzimkhulu local municipality in KwaZulu-Natal, specifically from the Harry Gwala District. A total of 56 participants took part in the study, including 28 WIL students and 28 mentors. This ensured representation from all departments within the municipality. Two separate sets of questionnaires were used to collect data from these two groups. Data analysis was performed using the Statistics Packaging for Social Sciences (SPSS) version 27. The study identified several challenges that currently hinder the effective implementation of WIL programmes within the municipality. As a result, it is recommended that the municipality provide training for WIL students and establish efficient monitoring and evaluation processes for the WIL programmes. Additionally, the municipality should involve students in WIL programmes in matters related to progressive initiatives and provide further support to enhance their ability to handle client services. It is also advised that the municipality prioritise the development of facilities and resources for WIL students to fully engage them in their work.